PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, DAN REPUTASI PERUSAHAAN TERHADAP NIAT BELI ULANG ( STUDI PADA PENUMPANG JASA TRAVEL BEJEU JEPARA ) - Emy Ratnasari, 11.05.51.0056 (Students Journal of Economic and Management, 2015)
The research attempts to know intence of quality service, price perseption, and company reputation in unity or partial to repurchase Intention. This research used primer data, the writer used quesioner as research instrument by SPSS calculation. Then, population of this research is all of passenger that ever utilize Travel Bejeu Service. the writer take 100 responden for sample. The Technic sampling of this research uses purposive sampling ,it is taken from appropriate sample that related. The equipment used silar deskriptive variabel and multiple linier regretion. The result for this research shows positive effect and not signifikan between service quality to Repurchase Intention. There is signifikan positive effect between price perception to repurchase intention. The sound of significant positive effect between company reputation toward repurchase intention. Keyword : Quality Service, Price Perception, Company Reputation, Repurchase Intention